2013
DOI: 10.1016/j.jspr.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of aflatoxin in peanuts (Arachis hypogaea Linnaeus) from markets in Western, Nyanza and Nairobi Provinces of Kenya and related market traits

Abstract: Fungal contaminants in major food staples in Kenya have negatively impacted food security. The study sought to investigate peanut market characteristics and their association with levels of aflatoxin in peanuts from Western, Nyanza and Nairobi Provinces of Kenya. Data were collected from 1263 vendors in various market outlets using a structured questionnaire, and peanuts and peanut products from each vendor were sampled and analyzed for aflatoxin levels. Thirty seven per cent of the samples exceeded the 10 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 23 publications
6
51
0
Order By: Relevance
“…This is in agreement with other studies reported in the literature on AFB 1 contamination of foods. This also portrays AFB 1 as a prevalent toxin in foods intended for human and animal consumption [17]. The results also showed that FB 1 , which is the most predominant fumonisins analogue was more abundant in maize before and after processing when compared to FB 2 .…”
Section: Discussionmentioning
confidence: 64%
“…This is in agreement with other studies reported in the literature on AFB 1 contamination of foods. This also portrays AFB 1 as a prevalent toxin in foods intended for human and animal consumption [17]. The results also showed that FB 1 , which is the most predominant fumonisins analogue was more abundant in maize before and after processing when compared to FB 2 .…”
Section: Discussionmentioning
confidence: 64%
“…Buying food is a common coping strategy during scarcities and as one moves farther along the supply chain from the source of food production, the likelihood of purchasing foods which may have been contaminated with aflatoxin increases, due to inadequate storage and improper handling. Mutegi and colleagues [9], for example, found that many of the storage facilities in market outlets in Western Kenya were dusty and poorly ventilated and that groundnuts were packed in plastic materials which were likely to encourage aflatoxin contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The level of risk of aflatoxin contamination is determined, in large part, by the quality of food drying, storage facilities and services at home and in the market place [5][6][7][8][9][10]. Foods stored in damp conditions and/or for prolonged periods of time (usually more than three months) can have increased levels of aflatoxin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While both A. flavus and A. parasiticus can produce aflatoxin B toxins, A. parasiticus exclusively produce the G1 and G2 aflatoxins [3]. Recent studies have shown that peanuts in Kenya are highly contaminated with aflatoxins [6], but information gaps exist on the distribution of aflatoxin producing Aspergillus species. Further, few studies have been done to characterize the fungi that produce the different types of aflatoxins.…”
Section: Introductionmentioning
confidence: 99%